Utility of 2-cyano-3-phenyl-2-propenoyl chloride as Michael’s acceptor in heterocyclic synthesis with mono- and bi-dentate nucleophiles - Shiba, Sayed Ahmed; Madkour, Hassan Mohamed Fawzy; Hamed, Ashraf Ahmed; Sayed, Hatem Mohamed; El-Hashash, Maher Abd El-aziz (European Journal of Chemistry, 2011)
(E) 2-Cyano-3-phenyl-2-propenoyl chloride reacts with nitrogen, oxygen and sulphur mono- and bi-dentate nucleophilic reagents to give the amide derivatives, the ester derivatives, as well as some heterocyclic systems, namely quinazolinone, pyridopyrimidine and benzothiazepine. Cyclization of some obtained amides affords the benzoxazinones, quinazolinone, whereas that of other amides yields oxadiazole and benzoxazole, respectively.